Effect Of Image Therapy On Reduction Of Anniversary Of DIII Students Midwifery Dealing With Writing Scientific - Nurlina; Ilhamsyah; Rahmatullah (Comprehensive Health Care, 2020)
According to World Helth Organization data, there are around 47.5 million people in the world who are affected by severe anxiety, in Indonesia alone there are around 14 million people aged 15 years and over, it is very possible to experience anxiety, overcoming anxiety by drawing activities is the right way to convey what which becomes a burden on the mind that causes anxiety through the process of scratching the image. The purpose of this study was to determine the effect of drawing therapy on reducing anxiety in D III midwifery students facing scientific papers at Stikes Panrita Husada Bulukumba 2018. This type of research is quantitative quasi-experimental with pre-test and post-test design methods. This study used a purposive sampling technique with research instruments using the HARS scale. This research was conducted for two meetings within 7 days. The paired T-test results obtained the first meeting = 0.001 (p-value <0.005) and the second meeting the paired T paired value = 0.001 (p-value <0.005). The study concludes that there is an effect of drawing therapy on reducing anxiety in midwifery DIII students facing scientific writing exams at Stikes Panrita Husada Bulukumba 2018.